2022
DOI: 10.1186/s12889-022-12715-x
|View full text |Cite
|
Sign up to set email alerts
|

Middle-aged preparation for healthy aging: a qualitative study

Abstract: Background Preparing for aging is investing resources in preparing to cope with the challenges that are expected to happen in older age. This will lead to an increase in the quality and well-being in aging. The present study was conducted to elucidate the preparation of the middle-aged people for healthy older age in Tehran, Iran. Methods The present study was performed with a qualitative approach and using semi-structured interviews with 23 Irania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Several qualitative studies have sought to understand the experiences of elderly individuals regarding social participation (5,9,13,18). Consistent with our findings, some previous studies have revealed that elderly social participation includes elements such as volunteer work, employment, cultural and social activities, and intergenerational interactions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several qualitative studies have sought to understand the experiences of elderly individuals regarding social participation (5,9,13,18). Consistent with our findings, some previous studies have revealed that elderly social participation includes elements such as volunteer work, employment, cultural and social activities, and intergenerational interactions.…”
Section: Discussionsupporting
confidence: 88%
“…It is projected that by 2050, this age group's share of the country's population will exceed 20%, totaling over 20 million people (8). As a result, there will be a growing population of elderly individuals experiencing physical limitations and disabilities, which will necessitate a greater demand for healthcare professionals and resources to adequately address their healthcare needs (4,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Microfinance groups are also conducive platforms for financial education for people at risk for inadequate financial literacy, such as women and racial and ethnic minorities (European Microfinance Network, 2012 ). It might be advantageous to start FHL training at midlife, as this is when people commonly prepare for retirement and set goals for healthy ageing (Solhi et al, 2022 ). Apart from FHL programs in the workplace of pre‐retirees, there is a need for concerted strategies in communities to reach more vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting FHL should consider an individual and group approach, as middle-aged/older adults may have common yet varying It might be advantageous to start FHL training at midlife, as this is when people commonly prepare for retirement and set goals for healthy ageing (Solhi et al, 2022). Apart from FHL programs in the workplace of pre-retirees, there is a need for concerted strategies in communities to reach more vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…Middle‐aged adults are facing physical and psychological ageing, and many of them experience the effects of chronic illness or psychological stress (Kong et al., 2022). A person's physical health in midlife affects his or her physical health in old age (Solhi et al., 2022a). How to maintain good physical and mental health is not only a concern for the older people but also a matter of great concern to the middle‐aged (Solhi et al., 2022b).…”
Section: Introductionmentioning
confidence: 99%